2000
DOI: 10.1016/s1463-4988(00)00045-2
|View full text |Cite
|
Sign up to set email alerts
|

Integration of varying responses of different organisms to water and sediment quality at sites impacted and not impacted by the petroleum industry

Abstract: The toxicity of surface waters and interstitial waters from sediments were determined at six study sites in Todos os Santos Bay, Bahia, Brazil, to evaluate the possibility of chronic environmental impact induced by 40 years of exposure to the local petroleum industry. Samples collected from four sites associated with the extraction, transportation and re®nement of petroleum, and from two control sites, were tested at seven three-month intervals. Toxicological assays using acute mortality of brine shrimp (Artem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 16 publications
1
8
0
5
Order By: Relevance
“…Between the evaluated end-points (acute and sublethal), the behavioral one (swimming speed alteration) confirmed to be a very useful tool to identify toxic effects when the level of toxicity is low (Faimali et al 2006;Garaventa et al 2010). Recently, many bioassays on sediment elutriate were conducted using larvae of marine organisms (Geffard et al 2002(Geffard et al , 2003(Geffard et al , 2004ASTM 1992;Nascimento et al 2000;Losso et al 2004;Onorati and Mecozzi 2004;Pelosi and Franchi 2003;Mueller et al 2003;Beiras et al 2003;Cheung et al 2003;Davoren et al 2005;Faimali et al 2006), but only few authors reported study on elutriate sediment toxicity assessment by the use of behavioral responses such as the swimming speed (Chapman et al 2002;Faimali et al 2006). A. salina and B. plicatilis seem not to be appropriate model organisms for the screening of low toxicity sediments, resulting to be less sensitive than A. amphitrite both considering acute and behavioral end-points (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Between the evaluated end-points (acute and sublethal), the behavioral one (swimming speed alteration) confirmed to be a very useful tool to identify toxic effects when the level of toxicity is low (Faimali et al 2006;Garaventa et al 2010). Recently, many bioassays on sediment elutriate were conducted using larvae of marine organisms (Geffard et al 2002(Geffard et al , 2003(Geffard et al , 2004ASTM 1992;Nascimento et al 2000;Losso et al 2004;Onorati and Mecozzi 2004;Pelosi and Franchi 2003;Mueller et al 2003;Beiras et al 2003;Cheung et al 2003;Davoren et al 2005;Faimali et al 2006), but only few authors reported study on elutriate sediment toxicity assessment by the use of behavioral responses such as the swimming speed (Chapman et al 2002;Faimali et al 2006). A. salina and B. plicatilis seem not to be appropriate model organisms for the screening of low toxicity sediments, resulting to be less sensitive than A. amphitrite both considering acute and behavioral end-points (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Except for a few studies on chemical sediment contamination (Tavares, 1986), and others related to the acute impacts of oil spills (CRA, 2000) and ecological surveys carried out between 1994-2000(Peso-Aguiar and Almeida, 1996Nascimento, 1996;Nascimento et al, 1998Nascimento et al, , 2000b, no integrative evaluation of the possible effects has been generated. Todos os Santos bay is bordered by an extensive mangrove ecosystem making the development of environmental diagnosis, techniques and monitoring programs priority for this bay.…”
Section: Advances On Sediment Quality Assessment In Brazil: Case Studiesmentioning
confidence: 99%
“…Toxic effects of porewater samples from several samples in the region of Ubatuba, SP, including a marina and gradients off several river mouths, were identified by the fertilization and embryological development tests with the sea urchin L. variegatus . Sediment contamination caused by oil transportation-and processingrelated operations was assessed by porewater analyses using early-life stage toxicity tests with the sea urchins L. variegatus and Echinometra lucunter, and the oyster C. rhizophorae (Zamboni, 1993;Nascimento et al, 2000b). The results indicated the presence of contaminants in toxic amounts.…”
Section: Sedimentsmentioning
confidence: 99%
“…The results indicated the presence of contaminants in toxic amounts. Acute mortality tests with brine shrimp nauplii (Artemia salina) conducted with samples from Bahia, showed good discriminatory power to distinguish among samples, but were consistently less sensitive than the embryological tests with oysters (Nascimento et al, 2000b). Mutagenicity analyses using the Ames test were also conducted in Brazil for the assessment of sediments to be dredged from an industrialized area and from Santos Harbor, SP (Roubicek et al, 1998).…”
Section: Sedimentsmentioning
confidence: 99%